Buckling and post buckling improvements of laminated composite plates using finite element method - A. Rasid, Zainudin (Scientific.Net, 2011)
The improvements of buckling and post-buckling behaviours of laminated composite plates were done by changing the composite related parameters such as the level of anisotropy, thickness to width ratio and boundary condition. In recent years, shape memory alloy has been used to achieve such improvements. A study is conducted on the buckling and post-buckling improvements of composite plates due to the combined effects of composite and shape memory alloy related parameters. Shape memory alloy wires are embedded within laminated composite plates and the amount of recovery stress induced by the shape memory wires is predicted using the Brinson’s model. A geometric non-linear finite element method is used to model the buckling and post-buckling behaviours of shape memory alloy composite plates and source codes are developed to solve the model. It is found that significant improvements in buckling and post-buckling behaviours of composite plates can be attained by combining the effect of shape memory alloy and composite related parameters.